Indetermination and Potentiality in Quantum Physics - Cruz Ortiz de Landázuri, Manuel (THÉMATA. Revista de Filosofía, 2019)
One of the main philosophical problems of quantum mechanics is understanding in what manner Schödinger’s wave function can said to be real. In this paper I explore the ways in which the Aristotelian notion of potentiality could be used to understand the reality of the wave function, as suggested by Heisenberg in some of his writings. For this reason I sketch some of the potential complications in the interpretation of wave function while trying to develop Aristotle’s philosophy of potentiality in relation to quantum mechanics. I will also attempt to demonstrate the connections of Popper’s account of propensities with the notion of potentiality.